SLC26 family: a new insight for kidney stone disease - Jialin Li; Jialin Li; Sigen Huang; Sigen Huang; Shengyin Liu; Shengyin Liu; Xinzhi Liao; Xinzhi Liao; Sheng Yan; Sheng Yan; Quanliang Liu (Frontiers in Physiology, 2023)
The solute-linked carrier 26 (SLC26) protein family is comprised of multifunctional transporters of substrates that include oxalate, sulphate, and chloride. Disorders of oxalate homeostasis cause hyperoxalemia and hyperoxaluria, leading to urinary calcium oxalate precipitation and urolithogenesis. SLC26 proteins are aberrantly expressed during kidney stone formation, and consequently may present therapeutic targets. SLC26 protein inhibitors are in preclinical development. In this review, we integrate the findings of recent reports with clinical data to highlight the role of SLC26 proteins in oxalate metabolism during urolithogenesis, and discuss limitations of current studies and potential directions for future research.